Structural, optical and radiation shielding parameters of sodium aluminium borate glasses modified with chromium oxide. (June 2023) - Abdelghany, A.M.; Alsaif, Norah A.M.; Madshal, M.A.; ElBatal, H.A.; Rammah, Y.S.; Awad, W.
Abstract: Samples of nominal composition xCr2 O3 . (60-x)B2 O3 .5Al2 O3 .35Na2 O: x = 0 (Cr0), 0.1 (Cr0.1), 0.2 (Cr0.2), 0.4 (Cr0.4), 0.6 (Cr0.6), 0.8 (Cr0.8), and 1 (Cr1) mol% were prepared via the traditional melt quenching route. Structural FTIR absorption spectra of the prepared glasses reveal distinct absorption bands which are characteristic of both triangular BO3 and tetrahedral BO4 groups within their varying wavenumber vibrational sites. The dopant chromium ions are observed to have no distinct variations on the FTIR spectra because of low dopant percent. Optical absorption characterization indicates that the undoped glass shows only UV absorption which is related to originating from unavoidable trace ferric ions present as impurities in the used chemicals. The Cr2 O3 -doped glasses reveal additional UV absorption at about 370-385 nm correlated with the hexavalent state of chromium, producing this distinct charge transfer band. Additionally, two visible bands are identified at about 420-400 nm and 580-640 nm originating from trivalent chromium ions with distorted octahedral coordination. Optical parameters including band gap, refractive index, molar refraction, and reflection losses were calculated together with optical dielectric properties, electronic and molar polarizability. In terms of radiation shielding capacity, increasing Cr2 O3 mol% of the sample encoded Cr1 that possessed the highest mass (μm) and linear (μ) attenuation coefficients, but the lowest half value layer (HVL) at low and high incident photon energy, results showed that Cr1 can be used in optical and radiation shielding safety. Highlights: X Cr2 O3 . (60- x )B2 O3 .5Al2 O3 .35Na2 O have been synthesized. Structural and physical properties of the prepared glasses were investigated. Optical properties were evaluated. Radiation safety parameters were examined.